Sulodexide Slows Down the Senescence of Aortic Endothelial Cells Exposed to Serum from Patients with Peripheral Artery Diseases - Patrycja Sosińska-Zawierucha (Cellular Physiology and Biochemistry, 2018)
Background/Aims: Aging of the arterial endothelial cells results in the appearance of their inflammatory phenotype, which may predispose patients to the acceleration of arteriosclerosis. We studied the effect of serum from patients with peripheral artery disease (PAD) on the senescence of human aortic endothelial cells (HAEC) and how that process is modulated by sulodexide. Methods: HAEC replicative aging in vitro was studied in the presence of 10% PAD-serum (PAD Group) or10%PAD serum and Sulodexide 0.5 LRU/mL (PAD-SUL group). In control group cells were cultured in medium supplemented with 10% fetal bovine serum. All studied parameters were evaluated at the beginning and at the end of the study, in all experimental groups. Population doubling time (PDT) was studied from the cells growth rate after repeated passages, and senescence-associated beta- galactosidase activity (SA-β gal activity) was measured with the fluorescence flow cytometry. Expression of IL6, vWF, p21 and p53 genes was measured with the real-time polymerase chain reaction (Real-Time PCR). Concentrations of IL6 and vWF were measured with the standard ELISA kits. Results: PAD serum accelerated the senescence of HAEC as reflected by increased, compared to control, expression of the IL6 gene (+43%, p<0.05) vWF gene (+443%, p<0.01), p21 gene (+ 124%, p<0.01) and p53 gene (+ 85%, p<0.01). Secretion of IL6 and vWF was higher in that group: + 101%, p<0.01 and + 78%, p<0.01, respectively, as compared to control. Also, SA-β gal activity was higher in the PAD group (+33%, p<0.05) than in the control group. In the PAD group PDT was longer (+108%, p<0.01) as compared to control. Simultaneous use of Sulodexide with PAD serum significantly reduced all the above described senescent changes in HAEC. Conclusions: PAD serum accelerates the aging of HAEC which may result in the faster progression of arteriosclerosis. Sulodexide reduces PAD induced senescence of HAEC, which results in lower inflammatory and thrombogenic activity of these cells.